The Relationship Between Anxiety and Coping Mechanisms in Type 2 Diabetes Mellitus Patients at Pekauman Health Center, Banjarmasin - Susandri, Hefly; Tjomiadi, Cynthia Eka F. (PROMOTOR, 2025)
A person with diabetes is twice as likely to experience anxiety. Type 2 diabetes patients with anxiety can experience unstable blood glucose levels continuously, leading to complications. Additionally, this anxiety condition may impact coping mechanisms and self-management. The purpose of this study is to determine the relationship between anxiety and coping mechanisms in Type 2 Diabetes Mellitus patients at the Pekauman Health Center in Banjarmasin. This study uses a quantitative method with a cross-sectional approach design, and sample collection uses a probability sampling technique with a total of 47 respondents. Data collection was done using the ZSAS (Zung Self-Rating Anxiety) questionnaire and a coping inventory questionnaire. The study results found that most Type 2 Diabetes Mellitus patients at the Pekauman Health Center experience mild anxiety, totaling 37 respondents (78.7%), and most employ adaptive coping mechanisms, totaling 42 respondents (89.4%). The Spearman rank test results show that the significant value (2-tailed) is p-value = 0.039 < 0.05, which indicates a relationship between anxiety and coping mechanisms in Type 2 Diabetes Mellitus patients at the Pekauman Health Center in Banjarmasin. Type 2 Diabetes Mellitus patients with mild anxiety tend to have adaptive coping mechanisms.